Research progress on the phytochemistry and bioactivity of Kaempferiae Rhizoma - ZENG Jia; TAN Hongyu; HE Xiangjiu; WANG Yihai (KeAi Communications Co., Ltd., 2021)
Kaempferiae Rhizoma (KR), also known as aromatic ginger or sand ginger, is the rhizome of the aromatic plant, Kaempferia galanga L. In traditional Chinese medicine, KR is prescribed for pain relief and promoting digestion. In folk medicine, it has a long history for treatment of hypertension, inflammation, and tumors. The plant is widely cultivated as an industrial crop and used as a spice in southern China. KR has attracted increasing interest in the last few decades because of its diverse composition and biologically active constituents. In this review, the volatile oil, terpenes, diarylheptanoids, phenolic acids, and flavonoids isolated from KR are summarized along with discussions of their biological significance for treatment of inflammation, pain, tumors, oxidative stress, and bacterial infection, and for insecticidal properties.